Ceramic green body, ceramic tile with close joint paving effect and preparation method and application of ceramic green body

By rationally matching chemical components, we develop a ceramic body with low expansion coefficient, low shrinkage and high strength, which solves the problem of ceramic tiles being easily hollowed out or arched after being paved with close joints, and realizes the close joint paving of ceramic tiles. effect and high yield.

CN119349985APending Publication Date: 2025-01-24GUANGDONG NEWPEARL CERAMIC GRP CO LTD +2
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411469513.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The thermal expansion coefficient of existing ceramic tiles is relatively large, resulting in hollowing or arching problems after being laid in tight joints, and the edge load-bearing capacity is reduced, which is prone to defects such as encounters during transportation and use.

Method used

Develop a ceramic blank body, and by rationally combined with Al2O3, SIO2, K2O, Na2O, Li2O, CAO, MGO and other chemical ingredients, it forms a low -expansion coefficient, low shrinkage and high -intensity ceramic body to ensure that ceramic tiles are in dense seams. It is not easy to cause damage and border defects after stickers.

Benefits of technology

It achieves the effect of dense joint paving of ceramic tiles. After paving, the gap can be controlled below 0.5mm, which improves the aesthetics and service life of ceramic tiles, ensures a high yield and is less likely to cause problems such as surface collapse during transportation and use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349985A_ABST
    Figure CN119349985A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of building ceramic tiles, and particularly relates to a ceramic green body, a ceramic tile with a close joint paving effect and a preparation method and application of the ceramic green body. The ceramic green body disclosed by the invention is prepared from the following chemical components in percentage by weight: 18.85 percent to 21.35 percent of Al2O3, 59.57 percent to 61.34 percent of SiO2, 2.68 percent to 4.56 percent of K2O, 1.68 percent to 3.54 percent of Na2O, 0.25 percent to 0.80 percent of Li2O, 2.34 percent to 3.65 percent of CaO, 1.24 percent to 2.45 percent of MgO, 0.54 percent to 1.34 percent of Fe2O3, 0.34 percent to 0.67 percent of TiO2 and the balance of ignition loss and impurities. According to the ceramic green body, under the combined action of all chemical components, all physical properties are optimized, the sealing effect of 0.5 mm or below can be achieved, and the problems occurring in the later period of paving can be solved, so that tight seam paving can be fundamentally achieved, the overall effect of ceramic tile paving is improved, and home furnishing is beautified.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building ceramic tiles, and in particular relates to a ceramic body, a ceramic tile with a close-seam paving effect, and a preparation method and application thereof. Background Art

[0002] With the upgrading of consumption, the requirements for ceramic tiles in home decoration are getting higher and higher, especially for large-area paving. The smaller the gap between tiles, the higher the aesthetics. In addition, it can also avoid the problem of dirt and grime caused by large gaps between tiles during use. In short, the close-jointed paving of tiles is popular with consumers, and the product also has a high added value. However, the thermal expansion coefficient of ceramic tiles currently on the market is large, that is, the phenomenon of thermal expansion and contraction is obvious. Once the close-jointed paving is carried out, it is easy to cause hollowing or arching of the tiles, and it is impossible to truly achieve complete close-jointed paving. By grinding the edges to make the area of ​​the lower surface of the ceramic tile slightly smaller than the area of ​​the upper surface, the problem of hollowing or arching caused by thermal expansion and contraction of the ceramic tile can be improved, but it cannot be fundamentally solved. In addition, the bearing capacity of the edges of the ceramic tiles is reduced, and it is easy to encounter defects such as collision during transportation and use. Summary of the invention

[0003] In view of the problems existing in the prior art, the purpose of the present invention is to provide a ceramic body, a ceramic tile with a close-seam paving effect, and a preparation method and application thereof. The ceramic body of the ceramic tile has a low expansion coefficient, a low shrinkage rate and high strength, which is conducive to close-seam paving, and has a high yield rate. It is not easy to have problems such as surface collapse during transportation and use.

[0004] Based on the above purpose, the technical solution adopted by the present invention is as follows:

[0005] In a first aspect, the present invention provides a ceramic body, comprising the following chemical components in weight percentage: Al2O3 18.85% to 21.35%, SiO2 59.57% to 61.34%, K2O 2.68% to 4.56%, Na2O1.68% to 3.54%, Li2O 0.25% to 0.80%, CaO 2.34% to 3.65%, MgO 1.24% to 2.45%, Fe2O30.54% to 1.34%, TiO2 0.34% to 0.67%, and the remainder being loss on ignition and impurities.

[0006] The glaze layer of ceramic tiles is relatively thin. Compared with the glaze layer, the ceramic body has a more critical influence on the close-jointed paving effect of ceramic tiles. Therefore, it is necessary to develop a ceramic body with a low thermal expansion coefficient. The above-mentioned ceramic body forms a relatively ideal expansion coefficient and shrinkage rate, as well as a higher strength by reasonably matching the above-mentioned components, thereby fundamentally realizing dense seam paving. Among them, Li2O has a strong fluxing effect, and combines with SiO2 and Al2O3 together with K2O and Na2O to react to form a glass phase with a lower expansion coefficient; compared with the monovalent oxides Li2O, K2O and Na2O, the divalent oxides CaO and MgO not only have a stronger high-temperature fluxing effect, but can also completely melt the free quartz in the body to form a SiO2 component calcium-magnesium glass phase. Compared with free quartz, the SiO2 component calcium-magnesium glass phase has a significantly lower thermal expansion coefficient, a lower expansion coefficient, and a relatively small firing shrinkage; Al2O3 and SiO2 are melted with the above-mentioned other oxides to form mullite crystals, and the mullite crystals are filled with glass phases and various oxide crystals, which greatly increase the strength of the body and ensure that after dense seam paving, the tiles are not easily damaged or have edge defects.

[0007] Preferably, the thermal expansion coefficient of the ceramic body is 6.30×10 -6 ~6.52×10 -6 / ℃, the shrinkage rate is 8.90% to 9.50%. The thermal expansion coefficient of the ceramic body can be selected to be 6.30×10 -6 / ℃、6.32×10 -6 / ℃、6.34×10 -6 / ℃、6.36×10 -6 / ℃、6.38×10 -6 / ℃、6.40×10 -6 / ℃、6.42×10 -6 / ℃、6.44×10 -6 / ℃、6.46×10 -6 / ℃、6.48×10 -6 / ℃、6.50×10 -6 / ℃、6.52×10 -6 / °C or an interval formed by any two of the above values. The shrinkage rate of the ceramic body can be selected to be 8.90%, 9.00%, 9.10%, 9.20%, 9.30%, 9.40%, 9.50% or an interval formed by any two of the above values.

[0008] Exemplarily, the thermal expansion coefficient of the ceramic body can be detected by the following method:

[0009] Prepare instruments and materials: An instrument suitable for measuring thermal expansion with a heating rate of 5℃ / min±1℃ / min; a vernier caliper or other suitable measuring instrument; and an oven capable of operating at 110℃±5℃.

[0010] Sample preparation: Press the ceramic green body powder with a moisture content of 6.5wt.% to 7.0wt.% into a cake-shaped green body with a thickness of 8mm and a diameter of 60mm. Cut two samples vertically from the center of the cake-shaped green body. The length of the sample is suitable for the test instrument. Both ends should be ground flat and parallel to each other. If necessary, the length of any side of the cross section of the sample should be ground to less than 6mm, and the area of ​​the cross section should be greater than 10mm. 2 The minimum length of the specimen is 50 mm.

[0011] Test process: The sample is dried at 110℃±5℃ to constant weight, and then the length of the sample is measured with a vernier caliper, accurate to 0.2% of the length. The sample is placed in an instrument for measuring thermal expansion, and heated from room temperature (such as 25℃) to 400℃ at a heating rate of 5℃ / min, while recording the changes in temperature and sample length.

[0012] Calculation of results: Thermal expansion coefficient α is 10 -6 / ℃, accurate to the first decimal place. The calculation formula is α=(ΔL / L0) / ΔT, where L0 is the length of the sample at room temperature, ΔL is the increase in length of the sample between room temperature and 400℃, and ΔT is the temperature rise.

[0013] Exemplarily, the shrinkage rate of the ceramic body can be detected by the following method:

[0014] Ceramic green body powder with a moisture content of 6.5wt.% to 7.0wt.% is pressed into a cake-shaped green body with a thickness of 0.8mm and a diameter of 60mm. The diameter R1 is measured with a vernier caliper. After sintering at 1185℃ for 1h, the diameter R2 of the sintered cake-shaped green body is measured again. The shrinkage rate = (R2-R1) / R1×100%.

[0015] Preferably, the raw materials for preparing the ceramic green body include the following components in parts by weight: 12 to 20 parts of black mud, 12 to 20 parts of washed ball clay, 4 to 8 parts of calcined coal gangue, 20 to 27 parts of potassium-sodium mixed sand, 6 to 10 parts of diopside, 4 to 8 parts of wollastonite, 5 to 10 parts of bentonite, 3 to 7 parts of ultra-white sand, 6 to 12 parts of cordierite, and 2 to 4 parts of lithium-containing potassium-sodium feldspar, wherein the whiteness of the ultra-white sand after sintering is above 85°.

[0016] Black mud includes the following chemical components in weight percentage: Al2O3 36.25% to 40.35%, SiO2 55.67% to 59.24%, K2O 0.34% to 0.50%, Na2O 0.40% to 0.62%, Fe2O3 0.54% to 0.98%, TiO2 0.60% to 0.80%, and the rest is loss on ignition and impurities. The main components of black mud are Al2O3 and SiO2, which provide the main skeleton of the green body. In addition, black mud contains more organic matter, which can increase the strength and plasticity of the green body, making it easier to shape and ensure the yield rate. According to the above chemical composition, the corresponding black mud can be selected, such as Guangdong black mud.

[0017] The washed ball clay is washed with water to remove impurities such as sand and tree roots, mainly providing Al2O3 and SiO2 components for the green body, playing a skeleton role and improving the forming performance of the green body.

[0018] The main components of calcined coal gangue are Al2O3 and SiO2. Because it has been calcined, it is easier to form mullite crystal phase after firing. The shrinkage rate after firing is low. At the same time, it can reduce the thermal expansion coefficient of the green body, making it easier to control the deformation of the green body, which is beneficial to the later dense seam paving.

[0019] The potassium-sodium mixed sand mainly provides potassium oxide and sodium oxide with strong fluxing effect for the green body, reduces the firing temperature of the formula, promotes the formation of the glass phase of the green body, and enables fast firing of the green body.

[0020] Diopside mainly provides divalent oxides such as CaO and MgO. On the one hand, it can increase the melting degree and better melt the free quartz in the formula, thus improving the problem of large thermal expansion coefficient caused by free quartz. On the other hand, the divalent oxides provided have a smaller thermal expansion coefficient than potassium-sodium flux, which is more conducive to the subsequent dense seam paving.

[0021] Wollastonite mainly provides the solvent CaO and the main skeleton component SiO2 for the green body. CaO has a lower thermal expansion coefficient than MgO.

[0022] The main components of bentonite are Al2O3 and SiO2, which can not only provide a skeleton for the green body, but also greatly increase the strength of the green body and improve the yield rate. At the same time, it has a smaller shrinkage rate after firing and can replace part of the black mud to reduce the shrinkage rate of the green body after firing.

[0023] Ultra-white sand mainly provides SiO2 for the blank, and after reacting with the flux, it will form glass phase SiO2, which constitutes the main component of the glass phase of the blank. Compared with free SiO2, glass phase SiO2 has a smaller thermal expansion coefficient, which is conducive to forming a blank with a lower thermal expansion coefficient and improving the close-joint paving effect of the product. The whiteness of the ultra-white sand after firing is above 85°, such as 85°, 87° or the interval formed by any two values ​​above. Exemplarily, the whiteness of the ultra-white sand after firing can be measured by the following method:

[0024] 1. Add the raw materials into water and obtain slurry by ball milling. The slurry has a fineness of 0.8-1.2 wt.% on a 320-mesh sieve and a water content of 35.8-37.0 wt.%;

[0025] 2. The slurry is dried and powdered, and pressed into a cylindrical cake-shaped material with a diameter of 6 cm and a thickness of 0.8 cm;

[0026] 3. Fire in a kiln at 1180°C for 65 minutes;

[0027] 4. After cooling, use a digital whiteness meter to directly measure the whiteness and display the whiteness data directly.

[0028] Cordierite contains Al2O3, SiO2 and MgO, which has the characteristic of a small thermal expansion coefficient. When used in the formulation, it can reduce the thermal expansion coefficient of the green body.

[0029] Lithium-containing potassium-sodium feldspar has a smaller thermal expansion coefficient. When combined with cordierite, it not only promotes the melting of the green body formula, but also greatly reduces the thermal expansion coefficient of the green body.

[0030] The ceramic body made with the above raw material formula has a low shrinkage rate and a low thermal expansion coefficient after firing, so that the ceramic tiles can be used for close-jointed paving; at the same time, it has high strength, ensuring a high yield rate and is not prone to surface collapse during transportation and use.

[0031] In a second aspect, the present invention further provides a ceramic tile, which includes the ceramic body, a glaze layer and a pattern layer; the ceramic body, the glaze layer and the pattern layer are stacked in sequence.

[0032] Preferably, the glaze layer comprises the following components in weight percentage: Al2O3 22.45% to 24.65%, SiO2 52.21% to 56.61%, K2O 2.13% to 4.24%, Na2O 1.89% to 3.45%, Li2O1.20% to 2.08%, CaO 2.04% to 3.65%, MgO 1.58% to 2.96%, BaO 5.24% to 8.54%, and the rest are loss on ignition and impurities.

[0033] The thermal expansion coefficient of the surface glaze layer is similar to that of the ceramic body, which can achieve a more ideal product deformation degree and is more conducive to the close-seam paving of the product.

[0034] Preferably, the thermal expansion coefficient of the glaze layer is 6.41×10 -6 ~6.90×10 -6 / ℃, the shrinkage rate is 9.20%~10.00%.

[0035] Exemplarily, the thermal expansion coefficient of the glaze used in the glaze layer can be measured by the following method:

[0036] Prepare instruments and materials: An instrument suitable for measuring thermal expansion with a heating rate of 5℃ / min±1℃ / min; a vernier caliper or other suitable measuring instrument; and an oven capable of operating at 110℃±5℃.

[0037] Sample preparation: Press the glaze powder with a moisture content of 6.5wt.% to 7.0wt.% into a cake-shaped body with a thickness of 8mm and a diameter of 60mm. Cut two samples vertically from the center of the cake-shaped body. The length of the sample should be suitable for the test instrument. Both ends should be ground flat and parallel to each other. If necessary, the length of any side of the cross section of the sample should be ground to less than 6mm, and the area of ​​the cross section should be greater than 10mm. 2 The minimum length of the specimen is 50 mm.

[0038] Test process: The sample is dried at 110℃±5℃ to constant weight, and then the length of the sample is measured with a vernier caliper, accurate to 0.2% of the length. The sample is placed in an instrument for measuring thermal expansion, and heated from room temperature (such as 25℃) to 400℃ at a heating rate of 5℃ / min, while recording the changes in temperature and sample length.

[0039] Calculation of results: Thermal expansion coefficient α is 10 -6 / ℃, accurate to the first decimal place. The calculation formula is α=(ΔL / L0) / ΔT, where L0 is the length of the sample at room temperature, ΔL is the increase in length of the sample between room temperature and 400℃, and ΔT is the temperature rise. (Same as the blank).

[0040] Exemplarily, the shrinkage rate of the glaze layer can be measured by the following method: Exemplarily, the shrinkage rate of the ceramic glaze layer can be detected by the following method:

[0041] The glaze powder with a moisture content of 6.5wt.% to 7.0wt.% is pressed into a cake-shaped body with a thickness of 8mm and a diameter of 60mm. The diameter R1 is measured with a vernier caliper. After firing at 1185℃ for 1h, the diameter R2 of the cake-shaped body after firing is measured again. The shrinkage rate = (R2-R1) / R1×100%.

[0042] In a third aspect, the present invention provides a method for preparing the ceramic tile, comprising the following steps:

[0043] Mix all the raw materials for preparing ceramic tiles, add water, a water reducing agent and a suspending agent, and ball-mill to obtain a ceramic body slurry;

[0044] The obtained ceramic body slurry is spray-dried to obtain a ceramic body powder;

[0045] Pressing the obtained ceramic green body powder into a shape and drying it to obtain a dry green brick;

[0046] The obtained dried bricks are glazed, patterned, fired, and edge-ground to obtain ceramic tiles.

[0047] Preferably, based on the total weight of all raw materials for preparing ceramic tiles, the weight of water is 38% to 40%, the weight of the water reducer is 0.3% to 0.4%, the weight of the suspending agent is 0.15% to 0.25%, and the weight of the multifunctional polymer solution is 0.1% to 0.2%.

[0048] Preferably, the water reducing agent includes at least one of water glass and sodium tripolyphosphate.

[0049] Preferably, the suspending agent includes at least one of sodium methyl cellulose and lignin.

[0050] Preferably, the specific gravity of the ceramic green body slurry is 1.75-1.85 g / mL, and the water content is 36 wt.%-38 wt.%.

[0051] Preferably, the moisture content of the ceramic green body powder is 6.0wt.% to 6.5wt.%.

[0052] Preferably, the strength of the dried brick is 1.8-2.4 MPa.

[0053] Preferably, the sintering temperature is 1178° to 1195° C., and the sintering time is 50 to 60 minutes.

[0054] In a fourth aspect, the present invention further provides an application of the ceramic tile in architectural decoration. The ceramic tile is suitable for close-jointed paving, and the gap between the ceramic tiles after paving can be controlled to be less than 0.5 mm, such as a maximum gap of 0.5 mm, 0.4 mm, 0.3 mm, 0.2 mm or 0.15 mm.

[0055] Compared with the prior art, the beneficial effects of the present invention are as follows: under the joint action of various chemical components, the ceramic body of the present invention has a low thermal expansion coefficient and a low shrinkage rate after firing, can achieve a sealing effect of less than 0.5 mm, and can solve the problems arising in the later stage of paving, thereby fundamentally achieving close-seam paving, increasing the overall effect of ceramic tile paving, beautifying the home, and having high strength and high yield, and is not prone to problems such as surface collapse during transportation and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 This is the SEM crystal phase image of the ceramic tile body of Example 1;

[0057] Figure 2 This is a photo of the ceramic tile of Example 1;

[0058] Figure 3 This is a photo of the ceramic tile of Comparative Example 8. DETAILED DESCRIPTION

[0059] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0060] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0061] In the present invention, the raw materials for preparing the green body and the glaze layer refer to the minerals or rocks used in making them, and do not include the processing aids used (such as suspending agents, water reducing agents).

[0062] Unless otherwise specified, the test methods used in the examples are all conventional methods; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels; the same raw materials have the same source.

[0063] Example 1

[0064] This embodiment provides a ceramic tile, and the preparation method thereof comprises the following steps:

[0065] (1) The following raw materials in parts by weight are mixed to obtain a mixed raw material for a ceramic body: 16 parts of Guangdong black mud, 16 parts of washed ball clay, 6 parts of calcined coal gangue, 23.5 parts of potassium-sodium mixed sand, 8 parts of diopside, 6 parts of wollastonite, 7.5 parts of bentonite, 5 parts of super white sand, 9 parts of cordierite, and 3 parts of lithium-potassium-sodium feldspar;

[0066] (2) adding 38% of the total weight of water, 0.3% of sodium tripolyphosphate and 0.2% of sodium carboxymethyl cellulose as a suspending agent to the mixed raw materials of the ceramic green body obtained in step (1), and subjecting the mixture to ball milling to obtain a ceramic green body slurry having a specific gravity of 1.78 g / mL and a water content of 36.5%;

[0067] (3) spray drying the ceramic green body slurry obtained in step (2) to obtain a ceramic green body powder having a moisture content of 6.5 wt.%;

[0068] (4) pressing the ceramic green body powder obtained in step (3) into a brick of required specifications through a press, and drying it to obtain a dried brick;

[0069] (5) The dried brick obtained in step (4) is glazed and patterned through a glaze line, and then fired at a temperature of 1185°C for 55 minutes. The edges are ground so that the angle between each side surface and its lower surface is 89.9°, thereby obtaining the target ceramic tile.

[0070] The ceramic body of the ceramic tile obtained in this embodiment contains the following chemical components in percentage by weight: Al2O3 20.10%, SiO2 60.45%, K2O 3.62%, Na2O 2.61%, Li2O 0.51%, CaO 2.99%, MgO 1.84%, Fe2O3 0.94%, TiO2 0.50%, and the rest are ignition loss and impurities;

[0071] The glaze in the ceramic tile obtained in this embodiment contains the following chemical components in percentage by weight: Al2O3 23.55%, SiO2 55.41%, K2O 3.18%, Na2O 2.67%, Li2O 1.54%, CaO 2.84%, MgO 2.27%, BaO 6.89%, and the rest are loss on ignition and impurities.

[0072] Example 2

[0073] This embodiment provides a ceramic tile, and its preparation method is different from that of embodiment 1 in that the amount of calcined coal gangue used in step (1) is 4 parts by weight. The ceramic body of the ceramic tile obtained in this embodiment contains the following chemical components in weight percentage: Al2O3 19.00%, SiO2 60.85%, K2O 3.582%, Na2O 2.63%, Li2O 0.51%, CaO 3.01%, MgO1.34%, Fe2O3 0.58%, TiO2 0.44%, and the rest are ignition loss and impurities.

[0074] Example 3

[0075] This embodiment provides a ceramic tile, and its preparation method is different from that of embodiment 1 in that the amount of calcined coal gangue used in step (1) is 8 parts by weight. The ceramic body of the ceramic tile obtained in this embodiment contains the following chemical components in weight percentage: Al2O3 21.09%, SiO2 59.67%, K2O 3.67%, Na2O 2.65%, Li2O 0.43%, CaO 2.69%, MgO1.99%, Fe2O3 0.95%, TiO2 0.48%, and the rest are ignition loss and impurities.

[0076] Example 4

[0077] This embodiment provides a ceramic tile, and its preparation method is different from that of embodiment 1 in that the amount of diopside used in step (1) is 6 parts by weight. The ceramic body of the ceramic tile obtained in this embodiment contains the following chemical components in weight percentage: Al2O3 20.08%, SiO2 60.55%, K2O 3.64%, Na2O 2.57%, Li2O 0.41%, CaO 2.35%, MgO 1.24%, Fe2O3 0.97%, TiO2 0.56%, and the rest are ignition loss and impurities.

[0078] Example 5

[0079] This embodiment provides a ceramic tile, and its preparation method is different from that of embodiment 1 in that the amount of diopside used in step (1) is 10 parts by weight. The ceramic body of the ceramic tile obtained in this embodiment contains the following chemical components in weight percentage: Al2O3 18.90%, SiO2 59.77%, K2O 3.47%, Na2O 2.89%, Li2O0.48%, CaO 3.63%, MgO2.44%, Fe2O3 0.59%, TiO2 0.59%, and the rest are ignition loss and impurities.

[0080] Example 6

[0081] This embodiment provides a ceramic tile, and its preparation method is different from that of embodiment 1 in that the amount of wollastonite used in step (1) is 4 parts by weight. The ceramic body of the ceramic tile obtained in this embodiment contains the following chemical components in weight percentage: Al2O3 21.32%, SiO2 60.47%, K2O 2.92%, Na2O 3.43%, Li2O 0.31%, CaO 2.40%, MgO 2.32%, Fe2O3 0.56%, TiO2 0.58%, and the rest are ignition loss and impurities.

[0082] Example 7

[0083] This embodiment provides a ceramic tile, and its preparation method is different from that of embodiment 1 in that the amount of wollastonite used in step (1) is 8 parts by weight. The ceramic body of the ceramic tile obtained in this embodiment contains the following chemical components in weight percentage: Al2O3 19.70%, SiO2 60.36%, K2O 3.54%, Na2O 2.60%, Li2O 0.38%, CaO 3.64%, MgO 2.05%, Fe2O3 1.03%, TiO2 0.35%, and the rest are ignition loss and impurities.

[0084] Example 8

[0085] This embodiment provides a ceramic tile, and its preparation method is different from that of embodiment 1 in that the amount of cordierite used in step (1) is 6 parts by weight. The ceramic body of the ceramic tile obtained in this embodiment contains the following chemical components in weight percentage: Al2O3 20.82%, SiO2 59.69%, K2O 3.43%, Na2O 2.76%, Li2O 0.34%, CaO 2.38%, MgO 1.26%, Fe2O3 1.04%, TiO2 0.63%, and the rest are ignition loss and impurities.

[0086] Example 9

[0087] This embodiment provides a ceramic tile, and its preparation method is different from that of embodiment 1 in that the amount of cordierite used in step (1) is 12 parts by weight. The ceramic body of the ceramic tile obtained in this embodiment contains the following chemical components in weight percentage: Al2O3 19.78%, SiO2 60.82%, K2O 3.82%, Na2O 3.51%, Li2O0.39%, CaO 3.55%, MgO2.43%, Fe2O3 0.84%, TiO2 0.48%, and the rest are ignition loss and impurities.

[0088] Example 10

[0089] This embodiment provides a ceramic tile, and its preparation method is different from that of embodiment 1 in that the amount of lithium potassium sodium feldspar used in step (1) is 2 parts by weight. The ceramic body of the ceramic tile obtained in this embodiment contains the following chemical components in weight percentage: Al2O3 21.02%, SiO2 60.96%, K2O 4.02%, Na2O 3.01%, Li2O 0.26%, CaO 2.40%, MgO1.64%, Fe2O3 0.60%, TiO2 0.38%, and the rest are ignition loss and impurities.

[0090] Embodiment 11

[0091] This embodiment provides a ceramic tile, and its preparation method is different from that of embodiment 1 in that the amount of lithium potassium sodium feldspar used in step (1) is 4 parts by weight. The ceramic body of the ceramic tile obtained in this embodiment contains the following chemical components in weight percentage: Al2O3 18.90%, SiO2 59.77%, K2O 3.87%, Na2O 3.11%, Li2O 0.58%, CaO 2.34%, MgO1.64%, Fe2O3 1.21%, TiO2 0.60%, and the rest is ignition loss and impurities.

[0092] Example 12

[0093] The present embodiment provides a ceramic tile, and the preparation method thereof is different from that of the embodiment 1 in that, in step (1), the mixed raw materials for the ceramic body are obtained according to the following raw material formula in parts by weight: 12 parts of Guangdong black mud, 12 parts of washed ball clay, 6 parts of calcined coal gangue, 27 parts of potassium-sodium mixed sand, 8 parts of diopside, 6 parts of wollastonite, 10 parts of bentonite, 7 parts of super white sand, 9 parts of cordierite, and 3 parts of lithium-containing potassium-sodium feldspar;

[0094] The ceramic body of the ceramic tile obtained in this embodiment contains the following chemical components in percentage by weight: Al2O3 18.89%, SiO2 60.77%, K2O 4.51%, Na2O 3.45%, Li2O 0.57%, CaO 3.55%, MgO 1.88%, Fe2O3 0.88%, TiO2 0.50%, and the rest are ignition loss and impurities;

[0095] The glaze of the ceramic tile obtained in this embodiment contains the following chemical components in weight percentage: Al2O3 24.65%, SiO2 53.21%, K2O 4.24%, Na2O 1.89%, Li2O 1.80%, CaO 3.65%, MgO 2.66%, BaO 7.54%, and the rest are loss on ignition and impurities.

[0096] Example 13

[0097] The present embodiment provides a ceramic tile, and the preparation method thereof is different from that of the embodiment 1 in that, in step (1), the mixed raw materials for the ceramic body are obtained according to the following raw material formula in parts by weight: 20 parts of Guangdong black mud, 20 parts of washed ball clay, 6 parts of calcined coal gangue, 18 parts of potassium-sodium mixed sand, 6 parts of diopside, 6 parts of wollastonite, 5 parts of bentonite, 3 parts of ultra-white sand, 9 parts of cordierite, and 3 parts of lithium-containing potassium-sodium feldspar;

[0098] The ceramic body of the ceramic tile obtained in this embodiment contains the following chemical components in percentage by weight: Al2O3 21.35%, SiO2 59.96%, K2O 2.71%, Na2O 1.95%, Li2O 0.34%, CaO 3.02%, MgO2.36%, Fe2O3 1.01%, TiO2 0.55%, and the rest are ignition loss and impurities;

[0099] The glaze of the ceramic tile obtained in this embodiment contains the following chemical components in weight percentage: Al2O3 22.45%, SiO2 56.59%, K2O 3.44%, Na2O 2.55%, Li2O 2.08%, CaO 2.94%, MgO 2.06%, BaO 7.54%, and the rest are loss on ignition and impurities.

[0100] Comparative Example 1

[0101] This comparative example provides a ceramic tile, and its preparation method is different from that of Example 1 in that the amount of calcined coal gangue used in step (1) is 2 parts by weight. The ceramic body of the ceramic tile obtained in this comparative example contains the following chemical components in weight percentage: Al2O3 18.14%, SiO2 61.30%, K2O 3.72%, Na2O 2.68%, Li2O 0.43%, CaO 2.78%, MgO1.99%, Fe2O3 0.99%, TiO2 0.59%, and the rest are ignition loss and impurities.

[0102] Comparative Example 2

[0103] This comparative example provides a ceramic tile, and its preparation method is different from that of Example 1 in that the amount of calcined coal gangue used in step (1) is 10 parts by weight. The ceramic body of the ceramic tile obtained in this comparative example contains the following chemical components in weight percentage: Al2O3 21.56%, SiO2 57.57%, K2O 3.82%, Na2O 3.51%, Li2O 0.30%, CaO 2.19%, MgO1.90%, Fe2O3 0.34%, TiO2 0.32%, and the rest are ignition loss and impurities.

[0104] Comparative Example 3

[0105] This comparative example provides a ceramic tile, and its preparation method is different from that of Example 1 in that the amount of diopside used in step (1) is 3 parts by weight. The ceramic body of the ceramic tile obtained in this comparative example contains the following chemical components in weight percentage: Al2O3 21.33%, SiO2 59.56%, K2O 3.72%, Na2O 2.97%, Li2O0.60%, CaO 1.87%, MgO 1.04%, Fe2O3 0.84%, TiO2 1.25%, and the rest are ignition loss and impurities.

[0106] Comparative Example 4

[0107] This comparative example provides a ceramic tile, and its preparation method is different from that of Example 1 in that the amount of diopside used in step (1) is 12 parts by weight. The ceramic body of the ceramic tile obtained in this comparative example contains the following chemical components in percentage by weight: Al2O3 17.99%, SiO2 59.23%, K2O 3.65%, Na2O 2.51%, Li2O0.51%, CaO 3.94%, MgO2.85%, Fe2O3 0.84%, TiO2 0.55%, and the rest are ignition loss and impurities.

[0108] Comparative Example 5

[0109] This comparative example provides a ceramic tile, and its preparation method is different from that of Example 1 in that the amount of wollastonite used in step (1) is 3 parts by weight. The ceramic body of the ceramic tile obtained in this comparative example contains the following chemical components in percentage by weight: Al2O3 21.45%, SiO2 58.56%, K2O 2.48%, Na2O 3.51%, Li2O0.38%, CaO 1.04%, MgO 2.54%, Fe2O3 1.54%, TiO2 0.67%, and the rest are ignition loss and impurities.

[0110] Comparative Example 6

[0111] This comparative example provides a ceramic tile, and its preparation method is different from that of Example 1 in that the amount of wollastonite used in step (1) is 10 parts by weight. The ceramic body of the ceramic tile obtained in this comparative example contains the following chemical components in weight percentage: Al2O3 21.43%, SiO2 61.04%, K2O 3.60%, Na2O 2.65%, Li2O0.25%, CaO 3.80%, MgO1.34%, Fe2O3 0.54%, TiO2 0.68%, and the rest are ignition loss and impurities.

[0112] Comparative Example 7

[0113] This comparative example provides a ceramic tile, and its preparation method is different from that of Example 1 in that the amount of cordierite used in step (1) is 4 parts by weight. The ceramic body of the ceramic tile obtained in this comparative example contains the following chemical components in weight percentage: Al2O3 18.90%, SiO2 60.45%, K2O 3.68%, Na2O 2.67%, Li2O 0.37%, CaO 1.40%, MgO 1.01%, Fe2O3 1.44%, TiO2 0.67%, and the rest are ignition loss and impurities.

[0114] Comparative Example 8

[0115] This comparative example provides a ceramic tile, and its preparation method is different from that of Example 1 in that the amount of cordierite used in step (1) is 16 parts by weight. The ceramic body of the ceramic tile obtained in this comparative example contains the following chemical components in weight percentage: Al2O3 18.10%, SiO2 60.54%, K2O 2.61%, Na2O 1.67%, Li2O0.42%, CaO 4.09%, MgO2.74%, Fe2O3 0.98%, TiO2 0.37%, and the rest are ignition loss and impurities.

[0116] Comparative Example 9

[0117] This comparative example provides a ceramic tile, and its preparation method is different from that of Example 1 in that the amount of lithium potassium sodium feldspar used in step (1) is 1 part by weight. The ceramic body of the ceramic tile obtained in this comparative example contains the following chemical components in percentage by weight: Al2O3 20.14%, SiO2 60.35%, K2O 4.60%, Na2O 1.11%, Li2O 0.02%, CaO 2.79%, MgO2.34%, Fe2O3 0.93%, TiO2 0.57%, and the rest are ignition loss and impurities.

[0118] Comparative Example 10

[0119] This comparative example provides a ceramic tile, and its preparation method is different from that of Example 1 in that the amount of lithium potassium sodium feldspar used in step (1) is 6 parts by weight. The ceramic body of the ceramic tile obtained in this comparative example contains the following chemical components in weight percentage: Al2O3 21.18%, SiO2 60.15%, K2O 3.22%, Na2O 3.11%, Li2O 0.92%, CaO 2.62%, MgO1.64%, Fe2O3 0.90%, TiO2 0.75%, and the rest are ignition loss and impurities.

[0120] Comparative Example 11

[0121] This comparative example provides a ceramic tile, and its preparation method is different from that of Example 1 in that the amount of super white sand used in step (1) is 2 parts by weight. The ceramic body of the ceramic tile obtained in this comparative example contains the following chemical components in percentage by weight: Al2O320.20%, SiO2 58.21%, K2O 3.88%, Na2O 3.21%, Li2O0.28%, CaO 3.45%, MgO 1.89%, Fe2O3 1.20%, TiO2 0.85%, and the rest are ignition loss and impurities.

[0122] Comparative Example 12

[0123] This comparative example provides a ceramic tile, and its preparation method is different from that of Example 1 in that the amount of super white sand used in step (1) is 9 parts by weight. The ceramic body of the ceramic tile obtained in this comparative example contains the following chemical components in percentage by weight: Al2O3 18.10%, SiO2 62.32%, K2O 3.60%, Na2O 1.88%, Li2O 0.38%, CaO 2.85%, MgO 1.68%, Fe2O3 1.04%, TiO2 0.66%, and the rest are ignition loss and impurities.

[0124] Comparative Example 13

[0125] This comparative example provides a ceramic tile, and its preparation method is different from that of Example 1 in that the amount of bentonite used in step (1) is 4 parts by weight. The ceramic body of the ceramic tile obtained in this comparative example contains the following chemical components in weight percentage: Al2O3 18.00%, SiO2 61.31%, K2O 3.88%, Na2O 2.78%, Li2O 0.39%, CaO 3.05%, MgO 2.08%, Fe2O3 1.24%, TiO2 0.58%, and the rest are ignition loss and impurities.

[0126] Comparative Example 14

[0127] This comparative example provides a ceramic tile, and its preparation method is different from that of Example 1 in that the amount of bentonite used in step (1) is 13 parts by weight. The ceramic body of the ceramic tile obtained in this comparative example contains the following chemical components in weight percentage: Al2O3 22.14%, SiO2 58.46%, K2O 3.24%, Na2O 2.65%, Li2O0.24%, CaO 3.24%, MgO2.55%, Fe2O3 0.65%, TiO2 0.54%, and the rest are ignition loss and impurities.

[0128] Comparative Example 15

[0129] This comparative example provides a ceramic tile, and its preparation method is different from that of Example 1 in that in step (1), the Guangdong black mud is replaced by an equal weight of raw ore mud. The ceramic body of the ceramic tile obtained in this comparative example contains the following chemical components in weight percentage: Al2O3 18.65%, SiO2 62.01%, K2O 3.54%, Na2O 2.07%, Li2O 0.29%, CaO 4.01%, MgO 1.14%, Fe2O3 1.65%, TiO2 0.69%, and the rest are ignition loss and impurities.

[0130] Test Example 1:

[0131] The ceramic tiles obtained from the above examples and comparative examples were subjected to the following performance tests:

[0132] Thermal expansion coefficient test of ceramic body or glaze layer: The ceramic body powder obtained in each embodiment and comparative example or the glaze powder (water content 6.5wt.%) is pressed into a cake-shaped body with a thickness of 8mm and a diameter of 60mm. Two samples are cut vertically from the center of the cake-shaped body. The length of the sample is suitable for the testing instrument. Both ends should be ground and parallel to each other. The sample is dried at 110℃±5℃ to constant weight, and then the length of the sample is measured with a vernier caliper to an accuracy of 0.2% of the length; the sample is then placed in an instrument for measuring thermal expansion and heated from 25℃ to 400℃ at a heating rate of 5℃ / min. The changes in temperature and sample length are recorded at the same time, and the thermal expansion coefficient of the ceramic body is calculated;

[0133] Shrinkage test of ceramic green body or glaze layer: The ceramic green body powder or glaze powder (water content 6.5wt.%) obtained in each embodiment and comparative example was pressed into a cake-shaped green body with a thickness of 0.8mm and a diameter of 60mm. The diameter R1 was measured with a vernier caliper. After sintering at 1185°C for 1h, the diameter R2 of the cake-shaped green body after sintering was measured again to calculate the shrinkage of the ceramic green body.

[0134] Test method for the strength of finished ceramic tiles (i.e., modulus of rupture): (a) Destructive strength: Select a square ceramic tile with a specification of 600mm*600mm*10mm, place it in a flexural tester to measure the destructive strength, set the span to 580mm, and gradually apply pressure. The force data required when the sample breaks is the destructive strength; (b) Modulus of rupture: The modulus of rupture detection method is the same as the above-mentioned destructive strength test method. After obtaining the destructive strength data, calculate it according to the following formula: Modulus of rupture = destructive strength * 580 (i.e., span) * 1.5 / 600 (i.e., the side length of the sample tile) * (square of the sample thickness), where the unit of destructive strength is N and the unit of sample thickness is mm.

[0135] The test results are shown in Table 1.

[0136] Table 1

[0137]

[0138]

[0139] Note: The top glaze layer in Examples 2 to 11 and Comparative Examples 1 to 15 is the same as the top glaze layer in Example 1, so the thermal expansion coefficient and shrinkage rate of the top glaze layer in Examples 2 to 11 and Comparative Examples 1 to 15 are not additionally measured.

[0140] From the above data, it can be seen that the green body of the ceramic tile of each embodiment has both low thermal expansion coefficient and shrinkage rate. For example, the thermal expansion coefficient of the green body is 6.30×10 -6 ~6.52×10 -6 / ℃, the shrinkage rate of the green body is 8.90% ~ 9.50%, which enables the ceramic tiles to be laid with close joints. After laying, the gap between the ceramic tiles can be controlled below 0.5mm. At the same time, these ceramic tiles have a high modulus of rupture, above 43MPa, a high yield rate, and are not prone to problems such as surface collapse during transportation and use.

[0141] In comparative example 1, the amount of calcined coal gangue used is too low, which is not conducive to the formation of mullite crystal phase, and makes the thermal expansion coefficient and shrinkage rate of the ceramic green body too high, and the modulus of rupture is too low, which is easy to cause damage; in comparative example 2, the amount of calcined coal gangue used is too high, the Al2O3 content is too high, the green body formula maturity temperature is too high, it is difficult to form a molten state, resulting in a small amount of crystals, and the green body is in a raw burning state, resulting in a high thermal expansion coefficient of the ceramic green body, making it difficult to form a close-seam paving effect.

[0142] In comparative example 3, the amount of diopside is too low, which is not conducive to the melting of free quartz in the formula, resulting in a high thermal expansion coefficient and shrinkage rate of the ceramic body; in comparative example 4, the amount of diopside is too high, the CaO and MgO contents are high, there are not too many Al2O3 and SiO2 oxides combined with the same valence, and the formed crystals are too few, which in turn leads to a high thermal expansion coefficient and shrinkage rate of the ceramic body.

[0143] In comparative example 5, the amount of wollastonite used is too low, resulting in a low CaO content in the ceramic body, causing its thermal expansion coefficient and shrinkage rate to be high; in comparative example 6, the amount of wollastonite used is too high, and the CaO content is too high, resulting in an excessively large shrinkage rate, making it difficult to control edge grinding after firing, resulting in poor close-seam paving effect.

[0144] In Comparative Example 7, the amount of cordierite used is too low, which is not conducive to the melting of the green body and affects the thermal expansion coefficient and shrinkage rate of the ceramic green body; in Comparative Example 8, the amount of cordierite used is too high, resulting in an overall expansion coefficient that is too small. Since the expansion coefficient of the glaze is basically difficult to change significantly, the brick shape is warped and uneven, and the sealing and paving effect is poor.

[0145] The amount of lithium potassium sodium feldspar contained in Comparative Example 9 is relatively low, which is not conducive to the melting of the green body and affects the thermal expansion coefficient and shrinkage rate of the ceramic green body; the amount of lithium potassium sodium feldspar contained in Comparative Example 6 is relatively high, and the melting of the green body is more serious during firing, resulting in a large shrinkage rate and poor product deformation, resulting in poor sealing effect after paving.

[0146] In Comparative Example 11, the dosage of ultra-white sand is relatively low, and the SiO2 content used to form the main skeleton is relatively low, resulting in a small amount of various crystals formed, affecting the thermal expansion coefficient and shrinkage rate of the ceramic body; in Comparative Example 12, the dosage of ultra-white sand is relatively high, which will result in the presence of more free quartz, affecting the thermal expansion coefficient and shrinkage rate of the ceramic body, resulting in poor sealing effect after paving.

[0147] In Comparative Example 13, the amount of bentonite used is too low, and the SiO2 and Al2O3 provided are too small, resulting in less mullite crystal phase formed, which affects the thermal expansion coefficient and shrinkage rate of the ceramic body; in Comparative Example 14, the amount of bentonite used is too high, and the firing shrinkage is too large, which affects the thermal expansion coefficient and shrinkage rate of the ceramic body.

[0148] In Comparative Example 15, raw ore mud is used to replace black mud. The raw ore mud contains more silica sand, and there is more free quartz after firing, which makes the thermal expansion coefficient and shrinkage rate of the ceramic body larger.

[0149] Figure 1 This is the SEM crystal photograph of the ceramic tile body of Example 1. It can be seen that the body has relatively rich crystals. According to the different shapes of the crystals, it can be seen that it contains more mullite crystals, monovalent oxide crystals and divalent oxide crystals. The existence of the crystals ensures that the body has a more suitable expansion coefficient and shrinkage rate, so that the product can achieve the effect of close-seam paving.

[0150] Figure 2 This is a photo of the ceramic tiles of Example 1 after paving. After paving, the maximum gap between the ceramic tiles is less than 0.2 mm.

[0151] Figure 3 This is a photo of the ceramic tiles of Comparative Example 7 after paving. The maximum gap between the ceramic tiles after paving is 0.6 mm.

[0152] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A ceramic body, characterized in that: The ceramic body comprises the following chemical components in weight percentage: Al2O3 18.85%-21.35%, SiO2 59.57%-61.34%, K2O 2.68%-4.56%, Na2O 1.68%-3.54%, Li2O 0.25%-0.80%, CaO 2.34%-3.65%, MgO 1.24%-2.45%, Fe2O3 0.54%-1.34%, TiO2 0.34%-0.67%, and the rest are ignition loss and impurities.

2. The ceramic body according to claim 1, characterized in that The thermal expansion coefficient of the ceramic body is 6.30×10 -6 ~6.52×10 -6 / ℃, the shrinkage rate is 8.90%~9.50%.

3. The ceramic body according to claim 1, characterized in that The raw materials for preparing the ceramic green body include the following components in parts by weight: 12 to 20 parts of black mud, 12 to 20 parts of washed ball clay, 4 to 8 parts of calcined coal gangue, 20 to 27 parts of potassium-sodium mixed sand, 6 to 10 parts of diopside, 4 to 8 parts of wollastonite, 5 to 10 parts of bentonite, 3 to 7 parts of ultra-white sand, 6 to 12 parts of cordierite, and 2 to 4 parts of lithium-containing potassium-sodium feldspar; wherein the ultra-white sand has a whiteness of more than 85° after sintering.

4. The ceramic body according to claim 3, characterized in that The black mud includes the following chemical components in weight percentage: Al2O3 36.25%-40.35%, SiO2 55.67%-59.24%, K2O 0.34%-0.50%, Na2O 0.40%-0.62%, Fe2O3 0.54%-0.98%, TiO2 0.60%-0.80%, and the rest are loss on ignition and impurities.

5. A ceramic tile, characterized in that: The ceramic tile comprises the ceramic body according to any one of claims 1 to 4, and further comprises a glaze layer and a pattern layer; the ceramic body, the glaze layer and the pattern layer are stacked in sequence.

6. The ceramic tile according to claim 5, characterized in that The surface glaze layer comprises the following components in percentage by weight: Al2O3 22.45% to 24.65%, SiO2 52.21% to 56.61%, K2O 2.13% to 4.24%, Na2O 1.89% to 3.45%, Li2O 1.20% to 2.08%, CaO 2.04% to 3.65%, MgO 1.58% to 2.96%, BaO 5.24% to 8.54%, and the rest are ignition loss and impurities.

7. The ceramic tile according to claim 5, characterized in that: The thermal expansion coefficient of the glaze layer is 6.41×10 -6 ~6.90×10 -6 / ℃, the shrinkage rate is 9.20%~10.00%.

8. The method for preparing a ceramic tile according to any one of claims 5 to 7, characterized in that: The following steps are involved: Mix all the raw materials for preparing ceramic tiles, add water, a water reducing agent and a suspending agent, and ball-mill to obtain a ceramic body slurry; The obtained ceramic body slurry is spray-dried to obtain a ceramic body powder; Pressing the obtained ceramic green body powder into a shape and drying it to obtain a dry brick; The obtained dried bricks are glazed, patterned, fired and edge-ground to obtain ceramic tiles.

9. The method for preparing a ceramic tile according to claim 8, characterized in that: Satisfy at least one of the following conditions (1) to (7): (1) Based on the total weight of all raw materials for preparing ceramic tiles, the weight of water is 38% to 40%, the weight of the water reducing agent is 0.3% to 0.4%, and the weight of the suspending agent is 0.15% to 0.25%; (2) The water reducing agent includes at least one of water glass and sodium tripolyphosphate; (3) The suspending agent includes at least one of sodium carboxymethyl cellulose and lignin; (4) The specific gravity of the ceramic body slurry is 1.75-1.85 g / mL, and the water content is 36 wt.%-38 wt.%; (5) The moisture content of the ceramic body powder is 6.0wt.% to 6.5wt.%; (6) The strength of the dried brick is 1.8 to 2.4 MPa; (7) The sintering temperature is 1178° to 1195°C, and the sintering time is 50 to 60 minutes.

10. Use of the ceramic tile according to any one of claims 5 to 7 in architectural decoration.

Citation Information

Patent Citations

  • Vitrified ceramic tile blank and vitrified ceramic tile preparation method thereof

    CN102924090A

  • Ceramic green body, ceramic plate and preparation method of ceramic green body

    CN113443893A

  • Lightweight anti-static ceramic tile and preparation method thereof

    CN114262209A

  • Ceramic blank based on lithium slag, ceramic green body, ceramic tile and preparation method of ceramic blank

    CN116715506A

  • Ceramic tile as well as preparation method and application thereof

    CN118545990A